TRANSPARENCY IN PUBLIC PROCUREMENT AS THE PRINCIPLE BINDING ON THE LEGISLATURE - Lastauskienė, Giedrė; Rudauskienė, Rimantė (Teisė, 2015)
Public procurement is one of the most important spheres of activities, controlled by the state. The state directly affects the market by using the tool of public procurement and becoming a participant in the procurement of services (supplies, works). Public procurement, considering its scale, has achieved an important significance as the market regulation tool and has a considerable impact on the whole economy of the state.Transparency and openness in public procurement – a priority goal of every government. Normally the principle of transparency imposes additional difficulties and administrative burden for contracting authorities. Moreover, in the face of economic-financial crisis any amendment of legal regulation, aggravating the status quo, generates additional economic tension between contracting authorities, suppliers and other entities. Therefore, all measures, assigned to the achievement of the goal of transparency, should be proportional and adequate.Successful implementation of electronic procurement shall be regarded as a positive result of the activities of the Fifteenth Government – electronic procurement implies adequate transparency, openness as well as economy, rationality of public procurement procedures. However, considering harsh economic situation, incapability to implement procedures of electronic auction in practice, to renounce publication of certain information regarding public procurement in the supplement Informaciniai pranešimai to the official gazette Valstybės žinios in a timely manner, incapacity to solve the problem of acquisitions of political parties appropriately account for failures of this Government.However, even bigger problems were created by systemic flaws of governmental activities. Under ruling of the Fifteenth Government legal regulation has become exceptionally unstable and chaotic. The chosen model of regulation is criticized as well: most changes in legal regulation, first of all, were adopted in a post-legislative form, making new regulation applicable solely to contracting authorities, subordinate or subject to the Government (at times – even without a proper evaluation that existing legal framework is not suitable for new post-legislative regulation), later on such regulation transforming into legislative regulation legally binding on all contracting authorities. Such flaws of law making and legislation caused a situation, where legal regulation became exclusively complicated, confused, contradictory and incomprehensible. It can obviously be stated that regulation of public procurement has been a process of attempts and correction of subsequent mistakes without a coherent and comprehensible strategy. Such a mess makes it difficult to ascertain which values were priorities for governments in the field of public procurement during the observed period.